Iron Oxide Nanoparticles Functionalized with Fucoidan: a Potential Theranostic Nanotool for Hepatocellular Carcinoma. (11th July 2022) - Geinguenaud, Frédéric; Sainte‐Catherine, Odile; Poirier, Florence; Besnard, Valérie; Haddad, Oualid; Chaubet, Frédéric; Lalatonne, Yoann; Lutomski, Didier; Sutton, Angela; Motte, Laurence
Abstract: Fucoidan is a natural sulfated polysaccharide with a large range of biological activities including anticancer and anti‐oxidation activities. Hepatocellular carcinoma is the fourth most common aggressive cancer type. The aim of this study was to investigate the bioactivity of free fucoidan versus its vectorization using nanoparticles (NPs) in human hepatoma cells, Huh‐7. Iron oxide NPs were functionalized with fucoidan by a one‐step surface complexation. NP cellular uptake was quantified by magnetic measurement at various extracellular iron concentrations. Cell invasion and migration were reduced with NPs while free fucoidan increases these events at low fucoidan concentration (≤0.5 μM). Concomitantly, a high decrease of reactive oxygen species production related with a decrease of the matrix metalloproteinase‐9 activity and an increase of its expression was observed with NPs compared to free fucoidan. A proteomic analysis evidenced that some fucoidan regulated proteins appeared, which were related to protein synthesis, N‐glycan processing, and cellular stress. To our knowledge, this is the first study which reveals such activity induced by fucoidan. These results pave the way for USPIO‐fucoidan‐NPs as potential theranostic nanotools for hepatocellular carcinoma treatment. Abstract : Ultra‐small super‐paramagnetic iron oxide nanoparticles (USPIO NPs) were functionalized with fucoidan, a natural sulfated polysaccharide mimicking glycosaminoglycans, to obtain a potential theranostic nanotool for hepatocellular carcinoma. The USPIO NPs act as vehicle and magnetic label to control fucoidan loading within cells.